Pengaruh Digital Marketing, Persepsi Harga Dan Citra Merek Terhadap Minat Beli Produk Uniqlo Di Semarang - Isna Familiana; Pesik, Jenifer; Sufiati, Sufiati; Bakhtiar, Rifki (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Lamappapoleonro, 2025)
The presence of digitalization in the economic sector, particularly in marketing, has led to the emergence of digital marketing. Consequently, business actors have begun utilizing e-commerce platforms to market their products and leveraging social media platforms such as Instagram and websites to facilitate transactions and create a perception of more affordable prices, as well as to establish a positive brand image to attract consumer interest in purchasing. The aim of this research is to determine the impact of digital marketing, price perception, and brand image on consumer buying interest in UNIQLO products in Semarang. This study employs a quantitative research method. Data were collected through the distribution of questionnaires to 128 UNIQLO consumers in Semarang. The results indicate that digital marketing, price perception, and brand image significantly influence consumer buying interest in UNIQLO products in Semarang.